ASSESSMENT OF SERUM PARAOXONASE-1 ENZYME ACTIVITY, MALONDIALDEHYDE AND VITAMIN-C IN ORAL PREMALIGNANCIES - Param, Kar; Kanchan, Mohod; Manish, Puttewar; Satish, Kumar (International Journal of Clinical and Biomedical Research, 2018)
Background: Oral premalignancies are a group of disease or syndromes which if left untreated can lead to cancer. It carries a great significance in Indian perspective. The actual figure of oral cancers arising from oral premalignancies is not known and to predict accurately the malignant transformations of them is still not possible. Oxidative stress is a known player behind cancerogenesis. Recently decreased Paraoxonase-1 activity and increased oxidative stress markers ware found to be associated with Oral Squamous Cell Carcinoma. So, there is a strong possibility of a similar finding in Oral Premalignancies too. Aim: This study aims to investigate the correlation between serum PON-1 activity and oxidative stress markers (MDA & Vitamin C) in patients with Oral Premalignancies. Material and Methods: A total of 62 patients with clinically diagnosed oral premalignant lesions and diseased controls were chosen for the study. Venous blood samples were collected and PON-1, MDA (in serum) & Vitamin c (in plasma) were analysed spectro-photometrically. Results: significant decreased serum PON-1 activity (P<0.05) and concomitant significantly increased serum MDA (P <0.05) and decreased Vitamin C levels (P<0.05) were observed in premalignancies compared to the controls. These finding were more pronounced in Oral Leukoplakia (OL) than in Oral Submucous Fibrosis (OSMF) with a significant difference. Mean levels of the analysed parameters differed accordingly in the clinical grades of oral premalignancies. Conclusion: It can be envisaged that serum PON-1 activity and increased oxidative stress might be a contributing factor behind pathogenesis and progression of Oral Premalignant Diseases.